OPPORTUNITIES AVAILABLE TO ACTIVE WOMEN ENTREPRENEURS TODAY (American Journal of Interdisciplinary Research and Development, 2024)
It is good that a female entrepreneur is a representative of the industry and brings additional income to her family. But today we need knowledge, training and experience in all areas. It is difficult to develop a business without mastering new technologies and modern approaches. In this regard, we can say that more than 400 non-governmental non-profit organizations created in our country have shown good experience in vocational training for women, involving them in entrepreneurial activities, and social assistance. This article provides thoughts and opinions about the opportunities available to active women entrepreneurs today.